Subjective memory impairment and well‐being in community‐dwelling older adults. Issue 1 (3rd March 2015) - Zuniga, Krystle E.; Mackenzie, Michael J.; Kramer, Arthur; McAuley, Edward
Abstract: Background: The relationship between subjective memory impairment (SMI), future cognitive decline, and negative health status provides an opportunity for interventions to reduce memory complaints in high‐risk groups. This study aimed to examine the relationship between SMI and indicators of well‐being in older adults enrolled in an exercise trial. Additionally, the study examined whether two different modes of exercise training, aerobic walking and non‐aerobic flexibility, toning, and balance, differentially influenced subjective memory across the trial. Methods: Community‐dwelling older adults ( n = 179, mean age = 66.4 years) were randomly assigned to a walking or flexibility, toning, and balance group for 12 months. Subjective memory, happiness, perceived stress, and symptom reporting were measured at baseline, 6 months, and 12 months. Results: A main effect of subjective memory indicated that individuals with the fewest memory complaints had lower perceived stress ( P < 0.001), lower physical symptom reporting ( P < 0.001), and higher happiness levels ( P < 0.001) across all measurement occasions. Both main and interaction effects of time and group on SMI were not significant, suggesting SMI remained stable across the intervention and was not significantly impacted by participation in exercise training. Conclusions: SMI was not responsive to exercise interventions, and the relationship between SMI and negative well‐being demonstrates a need for interventions to reduce memory complaints in high‐risk groups.